The Effect of Work Discipline on Employee Performance Mediated by Employee Job Satisfaction Dinas Pekerjaan Umum in Medan City - Herliza Syafiana; Tapi Rondang Ni Bulan; M. Fauzan Azhmy (LPPM STIE EKA PRASETYA, 2022)
The Public Works Office of Medan City is one of the agencies engaged in the repair of road infrastructure. Based on the information that the researchers obtained, one of the problems faced by the Medan City Public Works Office is the lack of discipline in the work of production employees in completing their work and reduced employee job satisfaction and a tendency to decline in the performance of general employees. The purpose of this study was to determine and analyze the effect of work discipline on employee performance mediated by employee job satisfaction at the Medan City Public Works Office. The number of population in this study was 214 people and the sample was 139 respondents using the Slovin method. The test used is path analysis or path analysis. The results of this study indicate that work discipline has no positive and significant effect on employee performance, work discipline has a positive and significant effect on employee job satisfaction, employee job satisfaction has a significant effect on employee performance and work discipline has a positif effect on employee performance throught employee job satisfaction.